2015
DOI: 10.1039/c5ra09581f
|View full text |Cite
|
Sign up to set email alerts
|

Diindenothienoacene–tetrathiafulvalene redox systems

Abstract: Extended tetrathiafulvalenes with central diindenothienoacene cores were prepared and studied for their redox and spectroelectrochemical properties, which depended strongly on the orientation of the thiophene rings. The cations undergo remarkably strong associations, rendering them attractive as redox-controllable tectons in supramolecular chemistry, and in one case crystals were grown by electrocrystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
(7 reference statements)
1
18
0
Order By: Relevance
“…The benzothieno‐fused molecule 4 is structurally similar and isoelectronic with 3 , whereas 5 is structurally similar and isoelectronic with 2 (when considering the π‐systems). The six molecules were synthesized by reacting the corresponding diones 6 – 10 with the Horner–Wadsworth–Emmons reagents 11 a or 11 b , prepared by an earlier reported procedure, followed by precipitation of the products. The yields for these transformations were moderate to good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzothieno‐fused molecule 4 is structurally similar and isoelectronic with 3 , whereas 5 is structurally similar and isoelectronic with 2 (when considering the π‐systems). The six molecules were synthesized by reacting the corresponding diones 6 – 10 with the Horner–Wadsworth–Emmons reagents 11 a or 11 b , prepared by an earlier reported procedure, followed by precipitation of the products. The yields for these transformations were moderate to good.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we studied the influence of substituting the central benzene ring of IF‐TTF with thiophene or thienothiophene units and found that the donor strengths and redox properties strongly depended upon the configurational arrangement of these units . Herein, we set out instead to first investigate systematically the influence of extending the π‐conjugation at the two ends of an extended TTF based on a central indacene framework by fusion of either naphthalene or benzothiophene units (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from the one-dimensional TTF-based molecules widely investigated in the past, we focused on combining dithiafulvene (DTF; "TTF half unit") and other functional molecular units to design cruciform-like molecular structures (that is, two orthogonally oriented π-systems). One aim was to achieve good and tunable conducting properties by virtue of the different conjugation pathways that exist between the individual parts of the molecule [17][18][19][20][21][22][23]. These DTF-based cruciform molecular wires have demonstrated potential promising applications in molecular electronics and also provided a good platform for the investigation of the dependence of conducting properties on their molecular structures [24][25][26].…”
mentioning
confidence: 99%
“…As we shall see in the following sections, insight into the structural differences of 1–5 is crucial in order to understand the electrochemical and spectroscopic results. Crystal structures of 2 a , 3 , and 4 have been presented earlier; however, no single crystals could be grown of 1 or of 5 . Therefore, the following discussion will instead be based on the optimized geometries (Figure ) obtained from B3LYP/6‐31G(d,p) calculations where the starting geometries for 2 a , 3 and 4 were taken from corresponding X‐ray structures while for 1 and 5 the spatial orientation of SR substituents was taken from 2 a and 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The orientations of the DTF units are either opposite of the sulfur in the nearest thiophene unit ( 1 and 3 ) or parallel ( 2 a , 2 b , 4 , and 5 ), introducing differences in the conjugation pathway between the two DTF units. Compounds 2 b , 3 and 4 have previously been investigated by some of us . In addition to expanding the series, in this full paper we present detailed in situ EPR/UV‐Vis‐NIR spectroelectrochemical studies in order to obtain a more detailed description of the influence exerted by one or more central thiophene rings and the influence of connecting the two dithiafulvene units in a cross‐conjugated or linearly conjugated manner.…”
Section: Introductionmentioning
confidence: 99%